2021
DOI: 10.1101/2021.03.30.21254459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Healthcare workers’ perceptions and attitudes towards the UK’s COVID-19 vaccination programme

Abstract: Objectives: To explore healthcare workers' (HCWs) perceptions and attitudes towards the COVID-19 vaccination programme in the UK, including their expectations, concerns and views on whether to promote vaccination to others. To understand the key factors shaping HCWs' attitudes towards COVID-19 vaccination in the UK. Design: This study was designed as a rapid qualitative appraisal integrating data from a review of UK policies and guidance on COVID-19 vaccination with data from in-depth semi-structured telepho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…This gives an opportunity to tailor vaccination messages around protecting family and loved ones, which may resonate more with HCWs than the standard expectation that they get vaccinated due to their role as health care professionals. As recommended in previous research, our study also highlights the need for timely and appropriate messaging by the government around vaccination to counter misinformation among HCWs as well as within the wider community (27). Healthcare settings have diverse job roles and promoting vaccine champions from different occupational groups (e.g.…”
Section: Discussionsupporting
confidence: 60%
“…This gives an opportunity to tailor vaccination messages around protecting family and loved ones, which may resonate more with HCWs than the standard expectation that they get vaccinated due to their role as health care professionals. As recommended in previous research, our study also highlights the need for timely and appropriate messaging by the government around vaccination to counter misinformation among HCWs as well as within the wider community (27). Healthcare settings have diverse job roles and promoting vaccine champions from different occupational groups (e.g.…”
Section: Discussionsupporting
confidence: 60%
“…This is consistent with research suggesting that healthcare workers themselves support the decision to prioritise vaccination for frontline health and social care workers and those at increased risk of vulnerability to infection. 34 As planning begins for further vaccination, careful communication regarding prioritisation should continue. We found high support for a second dose, suggesting the UK's decision to extend the Open access period between doses has not dented public confidence.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A study in the UK found that over 80% of surveyed PCPs felt that they were given sufficient autonomy to tailor their services to fulfil the needs of their patients and staff, which they valued (31) while also expressing desire for autonomy in the future. Another study highlighted differences in healthcare professionals' attitudes toward COVID-19 vaccines, showing that while some were keen to advocate vaccination to patients, others felt that it was not their role and decision should be left to the patient (32). However, the issues related to the importance of giving PCPs autonomy related to their personal safety at work during the pandemic have not been previously reported.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%